Estudio de factibilidad para la comercialización online de cargadores solares en la ciudad de Santiago de Cali (2020)
This work seeks to determine the feasibility of commercializing solar chargers online in the city of Santiago de Cali, this being the main objective of this study. For the development of the work, 4 specific objectives were established, key factors to carry out the feasibility study. It was established that, according to the field work developed in the first objective, 81% of the potential market would be willing to buy solar chargers, and it was determined that the means most frequently surveyed by respondents to acquire this class of technological products They are through virtual platforms such as web pages or social networks. The main objective of the technical analysis is to determine the technical and operational feasibility, taking into account the machines, supplies and resources available to satisfy potential demand. Accordingly, a prototype of the business website is designed and the process of commercialization of solar chargers, thus making strategic alliances with business suppliers. An organizational structure framed in processes was also proposed for the business and it was decided to link a single person who will be responsible for the commercialization of the solar chargers, and it is suggested to formalize the business as a natural person not responsible for VAT, taking into account that the product to be marketed is not obliged to pay tax taxes. Regarding the economic-financial study, the investment opportunity could be determined through the results obtained in the different financial projections, which finally presented an IRR of 50.9% reflecting the feasibility of executing the business, but demonstrating indicators to improve the profitability that can be obtained.